INFLUENCE OF COMPOSITION AND LYOPHILIZATION TIME ON PHYSICAL PROPERTIES OF HA/Cs/Coll/ HYDROXYPROPYL METHYLCELLULOSE BIOCOMPOSITES FOR BONE SCAFFOLDS - Purnaning, Dyah; Hurnah, Hurnah; Taufik S, Ahmad; Rahayu, Susi; Kurniawidi, Dian W.; Hadi, Kasnawi Al (Indonesian Physical Review, 2025)
Biomaterial implants are one of the alternatives to replace damaged organs in the body system temporarily (scaffolding) or permanently. Bone biomaterial implants can be obtained through the manufacture of HA/Cs/Coll (HA/Cs/Coll) biocompositeses with the addition of Hydroxypropyl Methylcellulose (HPMC) matrix. The objective is to evaluate how variations in material composition and lyophilization time affect the physical properties of the biocomposites, including density, compressive strength, Young’s modulus, and surface morphology. The manufacture of  biocomposites uses the mechanical thermal method for mixing materials and the freeze drying method for the biocomposites drying process. Composition ratios of HA:Cs/Coll were varied at 3:7, 5:5, and 7:3, while lyophilization durations were set at 24, 48, and 72 hours. Characterizations were performed through density measurements, mechanical testing using a Tensilon machine, and surface morphology analysis using a digital microscope. The results showed that the comparison of biocomposites with a ratio of 7:3 had the highest density of 0.150 gr/cm³, compressive strength of 0.046 MPa, and young modulus of 0.3 MPa. Meanwhile, the biocomposites that was lyophilized for 48 hours showed the best balance between a density of 0.145 gr/cm³, a compressive strength of 0.08 MPa, and a young modulus of 0.17 MPa. Morphological analysis revealed improved porosity and surface uniformity with longer freeze-drying times. Based on this, the resulting HA/Cs/Coll biocompositese has potential as an implant material but further research is needed to improve its mechanical properties by increasing the concentration of the binder, namely HPMC.